KEPASTIAN HUKUM PENGAWASAN MAJELIS PENGAWAS NOTARIS (MPN) TERKAIT NOTARIS YANG MELAKUKAN RANGKAP JABATAN. - Oktavia, Winda; Widjajaatmadja, Dhody AR.; Widyanti, Amelia Nur (LPPM Institut Pendidikan Nusantara Global, 2024)
The Notary Supervisory Council is a body that has the authority and obligation to carry out guidance and supervision of Notaries. The Notary Supervisory Council is divided into the Central Supervisory Council, Regional Supervisory Council, and Regional Supervisory Council. The aim of supervision is to ensure that Notaries when carrying out their official duties fulfill all requirements relating to the implementation of the duties of a Notary. Supervision by the Notary Supervisory Board is carried out repressively. The theory used in this research is the Theory of Legal Certainty according to Gustav Radbruch, the Theory of Legal Supervision according to Lyndal F. Urwick and Stephen Robein. The method used in this research is normative juridical (library law research or secondary data with primary, secondary and tertiary legal material sources), coupled with interviews as complementary data. The research approaches used are statutory, case, analytical and conceptual approaches with legal material collection techniques carried out by identifying and inventorying legal rules, book literature and other legal materials. Legal material analysis techniques are carried out using grammatical legal interpretation and systematic interpretation. From the results of the research, it was concluded that in order to carry out the function of supervision and guidance for Notaries, the Notary Supervisory Council has the role of supervising the party not only aimed at complying with the code of ethics but also has a broader aim, namely that the Notary in carrying out his duties fulfills the requirements. determined by statutory regulations for the protection of the interests of the community it serves. The Notary Supervisory Council has the authority to supervise, examine and impose sanctions on Notaries. In the event that a Notary commits a violation of holding multiple positions, the Notary is not authorized to make a deed and the deed cannot be treated as an authentic deed, so the deed is only a private deed.